2021
DOI: 10.1007/s42729-021-00620-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Individual and Consortia Plant Growth Promoting Bacteria on Physiological and Enzymatic Mechanisms to Confer Drought Tolerance in Maize (Zea mays L.)

Abstract: Mitigation strategies based on plant–microbe interactions to increase the performance of plants under water-deficit conditions are well documented. However, little is known about a suitable consortium of bacterial inoculants and underlying physiological and enzymatic events to improve drought tolerance in maize. We performed laboratory and pot experiments to understand the synergistic interactions among plant growth-promoting bacteria to alleviate the drought-induced damages in maize. Initially, ten bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“… Abdelaal et al (2021) reported similar findings, indicating that the application of chitosan significantly decreased electrolyte leakage. Furthermore, PGPR has been shown to reduce electrolyte leakage in drought-stressed plants ( Saleem et al , 2021 ). Synergistic combinations may improve drought tolerance in rice plants by reducing proline accumulation and electrolyte leakage while concurrently increasing the activities of antioxidant enzymes as well as chlo­rophyll and relative water contents.…”
Section: Resultsmentioning
confidence: 99%
“… Abdelaal et al (2021) reported similar findings, indicating that the application of chitosan significantly decreased electrolyte leakage. Furthermore, PGPR has been shown to reduce electrolyte leakage in drought-stressed plants ( Saleem et al , 2021 ). Synergistic combinations may improve drought tolerance in rice plants by reducing proline accumulation and electrolyte leakage while concurrently increasing the activities of antioxidant enzymes as well as chlo­rophyll and relative water contents.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of PGPR on plant health have been well documented in literature; however, the inherent complexity of PGPR interactions with the environment, native flora, and crop-specific conditions contributes to inconsistent outcomes [ 46 , 47 ]. To address these challenges, contemporary research efforts increasingly focus on the use of specific combinations of PGPR [ 23 , 48 50 ] with a wide spectrum of modes of action, that is sufficiently robust to counter environmental factors, [ 49 , 51 ]. For instance, recent studies by Calvo et al [ 52 ] have highlighted the efficacy of tailored PGPR blends in enhancing nutrient uptake and stress tolerance in various crop species.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest that the final properties of the SynComs were not strictly the sum of effects of the strains composing it. The assembly of strains can confer new functionalities, as shown in plant studies where bacterial consortia increased photosynthetic and antioxidant systems compared to individual bacteria [ 54 , 55 ]. Conversely, the assembly of strains may lead to a loss of functions.…”
Section: Discussionmentioning
confidence: 99%